Bioefficacy of neonicotinoid insecticides against insect pests of Okra (Abelmoschus esculentus(L.) Moench) - Jijisha P K (Department of Agricultural Entomology, College of Horticulture, 2014)
An investigation on “Bioefficacy of neonicotinoid insecticides against insect pests of okra (Abelmoschus esculentus (L.) Moench)” was undertaken in the Department of Agricultural Entomology, College of Horticulture, Vellanikkara, Kerala Agricultural University during 2013- 2014. The study was carried out by conducting two field experiments at the Instructional Farm, College of Horticulture in two seasons viz., April 2013 to July 2013 and October 2013 to January 2014. Two neonicotinoid insecticides - thiamethoxam and imidacloprid - were fieldevaluated for their biological efficiency against major insect pests of okra, safety to naturaenemies, influence on plant growth parameters and terminal residues in okra fruits. The twoinsecticides were applied in three methods viz., seed treatment (ST), two foliar treatments (2FT) and a combination of seed treatment followed by a single foliar treatment (ST+FT). Thetreatments comprised of ST thiamethoxam 30FS @ 3 g a.i. kg -1 (T1) and ST imidacloprid48FS @ 6 g a.i. kg -1 (T2) before sowing, two foliar sprayings ( 2FT) with thiamethoxam25WG @ 25g ai ha -1 (T3) and imidacloprid 70WG @ 25 g a.i. ha -1 (T4) at 15 and 30 daysafter sowing (DAS) and a combination of seed treatment followed by a foliar spraying(ST+FT) with thiamethoxam (T5) and imidacloprid (T6) at 30 DAS. A standard checkinsecticide quinalphos 25EC @ 250 g a.i. ha -1 as two foliar sprayings (FT) at 15 and 30DAS (T7) along with an untreated control (T8) were also included in the field experiment. Both thiamethoxam and imidacloprid were found to be significantly effective than quinalphos against Amrasca biguttula biguttula Ishida in okra. All the three methods of application with thiamethoxam and imidacloprid showed equal effectiveness upto 30 DAS. However, both the foliar treatment and the combination of seed treatment followed by a single foliar treatment with thiamethoxam proved to be equally effective throughout the season to A. biguttula biguttula. Thiamethoxam and imidacloprid by all the three application methods (seed treatment, foliar treatment and combination of seed treatment followed by foliar treatment) were equally effective against Aphis gossypii Glover upto 25 DAS. From 30 to 50 DAS, two foliar sprayings at 25 g a.i. ha -1 revealed a highest reduction of 88.49 per cent in the population of A. gossypii. Two foliar sprayings with imidacloprid 70 WDG @ 25 g a.i. ha-1 at 15 and 30 DAS recorded the lowest population of Bemisia tabaci Gennadius and least leaf damage by Sylepta derogata Fabricius in okra. Thiamethoxam 25WDG with two foliar sprayings (2 FT) @ 25 g a.i. ha -1 at 15 and 30 DAS significantly reduced the shoot and fruit damage by Earias vitella Fabricius. With regard to the impact of thiamethoxam and imidacloprid on natural enemies, two foliar sprayings with thiamethoxam at 25 g a.i. ha -1 showed highest coccinellid population in the first season. In the second season, seed treatment with thiamethoxam @ 3 g a.i. kg